Pengembangan Kapasitas Manajerial UMKM untuk Meningkatkan Daya Saing Melalui Inovasi Teknologi - Indah Monalisa; Reika Triana Yohana Sidabutar; Tasya Novi Ardana; Fatio D Situmorang (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
Micro, Small, and Medium Enterprises (UMKM) play a crucial role in the national economy. However, significant challenges such as limited resources, market access, and inadequate managerial capabilities remain obstacles to enhancing competitiveness. Developing managerial capacity through technological innovation has become a strategic solution for UMKM to survive and grow in the digital era. This study aims to analyze the importance of developing managerial capacity in improving UMKM competitiveness through technology adoption. The research method used is a literature review and analysis of secondary data from various relevant sources. The findings indicate that technological innovation in managerial aspects, such as the use of digital systems for marketing, finance, and operations, positively impacts efficiency and competitiveness. Therefore, appropriate strategies are needed to enhance UMKM managerial capacity in adopting technology to compete globally.